Prapenuntutan dalam Penegakan Hukum Perkara Tindak Pidana Narkotika - Putra, Dedetri; Marpaung, Zaid Alfauza (Fakultas Tarbiyah IAI Nasional Laa Rooiba, 2024)
The uncommon expansion in opiates wrongdoing cases has raised worries for the general population. So during the time spent looking at a lawbreaker act, beginning from request, examination, and indictment should go through. The Criminal Strategy Code expresses that on the off chance that the aftereffects of the examination are fragmented, the documents will be returned, this is called pre-arraignment. In any case, practically speaking, different issues and hindrances are as yet found, in particular that examiners never again have the position to do examinations, particularly in opiates violations. By utilizing regularizing juridical examination strategies with administrative and context oriented approaches. In view of this depiction, the issues examined are pre-arraignment plans in the criminal examination case cycle and what authority the Public Examiner has with respect to pre-arraignment in criminal demonstrations, particularly opiates violations. The examination results show that pre-arraignment is directed in KUHAP Article (14) letter b and Regulation no. 16 of 2004 concerning the Examiner's Office of the Republic of Indonesia, to be specific the arrival of case records from the overall assessment to agents, on the grounds that the overall assessment was of the assessment that the consequences of the examination were, fragmented joined by guidelines for finishing them.